THE GHOST EMPEROR'S NEW CLOTHES : A GRAPHIC NOVEL - Harper, Benjamin; Lopez, Alex; Robbins, Mandy (North Mankato, Minnesota : Stone Arch Books, a Capstone imprint, 2021)
The ghost of a vain emperor is causing trouble in the local village shops. But famed ghost hunters are on the case. They plan to catch the ghost on camera and win a $1-million-dollar prize! In life, the emperor was fooled into going out with no clothes. Trickster tailors convinced him he was wearing the finest silks in all the land! Could professional ghost hunters use the same tactics to win the prize money? Experience the story of The Emporer's New Clothes like never before in this graphic novel retelling for kids. Each Far Out Fairy Tales adventure includes info on the original tale, a guide to the story's twists, and visual discussion questions to critically engage readers.
Interest age level: Ages 8-11.
Keywords: Ghosts -- Comic books, strips, etc. -- Juvenile fiction; Emperors -- Comic books, strips, etc. -- Juvenile fiction; Ghost comics